ANALISIS PENGATURAN KEAMANAN DATA PRIBADI DI INDONESIA - Mirnayanti Mirna; Judhariksawan; Maskum (JURNAL ILMIAH LIVING LAW, 2023)
This study aims to analyze the regulatory invitation regarding the protection of personal data and the urgency of the bill Personal Data Protection in Indonesia. The type of research used by the author is the type of legal research normative approach to the method of legislation, approach case, and conceptual. The legal materials used consist of: primary law, namely related laws and regulations, as well as material secondary law, namely book literature, legal journals, articles and bills PDP. The entire legal material is analyzed qualitatively and presented descriptively. The results of the study answered that: 1) arrangements regarding security Personal data in positive law in Indonesia is spread across various fields sectoral laws and regulations covering 32 regulations scattered in the Human Rights Act, sector telecommunications and informatics, public service sector, sector health, population and archives sector, banking sector, finance, and taxation, trade and industrial sectors as a form of protection of personal data and public privacy. cause there is no harmonization at the normative level as well as the absence of stronger legal certainty for the community because there is no law that specifically regulates related personal data protection. 2) The legal politics of the formation of the PDP Bill from In terms of the formation process, it has been proposed since 2014. As of January 24, 2020, the PDP Bill has been signed by President Joko Widodo and will then be discussed in the DPR. PDP Bill This will be proposed in the DPR's priority national legislation program for the period 2019-2024. In terms of substance related to legal protection arrangements In the PDP Bill, it contains provisions related to the rights owned by the community for the data. Key Words: Security, Personal Data, Positive Law, PDP Bill.